THE STUDENTS’ READING PREFERENCES AND INFLUENCING FACTORS IN HIGHER EDUCATION - Yulmiati Yulmiati; Lira Hayu Afdetis Mana; Melvina Melvina; Yelfiza Yelfiza (English Study Program University of Pasir Pengaraian, 2026)
The changing landscape of reading in the digital era has significantly reshaped students’ reading behaviours, making it an essential area of academic inquiry. Despite extensive research on literacy, limited studies have comprehensively examined how shifting media environments influence students’ reading preferences alongside the underlying factors driving these changes. This study aims to analyze students’ reading preferences and investigate the factors affecting their choices in academic reading practices. Employing a quantitative descriptive design for reading preferences and qualitative design for affecting factors. The data were collected through a structured questionnaire administered to 154 university students and analyzed using descriptive statistical techniques to identify patterns of reading preferences and interview to see the influencing factors. The findings reveal that students tend to prefer digital reading materials because of their accessibility, convenience, flexibility, and multimedia features. However, printed materials remain important for deep comprehension, concentration, and long-duration reading. The study also found that technological familiarity, academic workload, time efficiency, personal motivation, and accessibility significantly influence students’ reading preferences. The novelty of this study lies in its comprehensive examination of both reading format preferences and the multidimensional factors shaping students’ reading behaviour within contemporary academic contexts. The study highlights the importance of integrating digital and print resources in higher education to support diverse learning needs and promote more effective literacy development strategies.